Π-Conjugated stannole copolymers synthesised by a tin-selective Stille cross-coupling reaction. Issue 10 (12th April 2021) - Ramirez y Medina, Isabel-Maria; Rohdenburg, Markus; Rusch, Pascal; Duvinage, Daniel; Bigall, Nadja C.; Staubitz, Anne
Abstract : The synthesis of four well-defined conjugated polymers TStTT1–4 containing unusual heterocycle units in the main chain, namely stannole units as building blocks, is reported. Abstract : The synthesis of four well-defined conjugated polymers TStTT1–4 containing unusual heterocycle units in the main chain, namely stannole units as building blocks, is reported. The stannole–thiophenyl copolymers were generated by tin-selective Stille coupling reactions in nearly quantitative yields of 94% to 98%. NMR data show that the tin atoms in the rings remain unaffected. Weight-average molecular weights ( M w ) were high (4900–10 900 Da and 9600–21 900 Da); and molecular weight distributions ( M w / M n ) were between 1.9 and 2.3. The new materials are strongly absorbing and appear blue-black to purple-black. All iodothiophenyl–stannole monomers St1–4 and the resulting bisthiophenyl–stannole copolymers TStTT1–4 were investigated with respect to their optoelectronic properties. The absorption maxima of the polymers are strongly bathochromically shifted compared to their monomers by about 76 nm to 126 nm in chloroform. Density functional theory calculations support our experimental results of the single stannoles St1–4 showing small HOMO–LUMO energy gaps of 3.17–3.24 eV. The optical band gaps of the polymers are much more decreased and were determined to be only 1.61–1.79 eV. Furthermore, both the molecular structures of stannoles St2 and St3 from single crystal X-ray analyses and the results of the geometry optimisation by DFT confirm the high planarity of the molecules backbone leading to efficient conjugation within the molecule.